A new critical habitat for conservation of the White-bellied Heron Ardea insignis Hume, 1878 (Aves: Ardeidae) from Bhutan - Karma Wangdi (Journal of Threatened Taxa, 2017)
The White-bellied Heron Ardea insignis is listed as Critically Endangered on the IUCN Red List of Threatened Species due to its extremely small and rapidly dwindling population. Bhutan is home to the highest number of White-bellied Heron and the species is distributed patchily across 11 different sites in central and south-west Bhutan. In this note, we present the first evidence of the species in eastern Bhutan, on the Drangmechhu River in Trashi Yangtse district. The finding extends the distribution of the species in Bhutan and recognizes one more potentially critical habitat for immediate conservation attention. As elsewhere, the new site is found to be primarily threatened by hydropower development. The need for conservation initiatives for the species is immediate and highly recommended.